Development of Quizwhizzer-Assisted Educational Game-Based Learning Evaluation Tools in Informatics Subjects in Junior High Schools - Pertiwi, Ragil Elva; Zen, Zelhendri; Darmansyah, Darmansyah; Amilia, Winanda (JUPE : Jurnal Pendidikan Mandala, 2023)
This study discusses how the process of development, validity testing and practicality testing of educational game-based learning evaluation tools on the subject matter of informatics materials Information Technology and Communication at the State High School 39 Padang. This type of research is Research and Development (R&D). (Analysis, Design, Development, Implementation, and Evaluation). The study conducted validity tests with 3 experts and the number of students practicality tests as much as 20 people. The results of the research showed that Quizwhizzer's educational game-based learning evaluation tool is worthy of use. From the data the validity of media expert 1 was 95.2%, media expert 2 was 97.6%, material expert 95.2, and the test results of 86% in the category “Very Practical”. It can be concluded that the evaluation tool based on educational games with Quizwhizzer in computer science subjects is worthy of use in the class VIII of SMP N 39 Padang.